The Mechanism of Increasing The Investment Attractiveness of Industrial Enterprises Improvement - Alisherovna, Mukhitdinova Kamala (Indonesian Journal Publisher, 2024)
The article promotes the ways of increasing the efficiency of the country's investment activities, and the methods of applying foreign experience to our republic are described in detail.